Evaluating methods to define place of residence in Canadian administrative data and the impact on observed associations with all-cause mortality in type 2 diabetes - Danielle K Nagy; Lauren C Bresee; Dean T Eurich; Scot H Simpson (BMC Medical Research Methodology)
Abstract Purpose An individual’s location of residence may impact health, however, health services and outcomes research generally use a single point in time to define where an individual resides. While this estimate of residence becomes inaccurate when the study subject moves, the impact on observed associations is not known. This study quantifies the impact of different methods to define residence (rural, urban, metropolitan) on the association with all-cause mortality. Methods A diabetes cohort of new metformin users was identified from administrative data in Alberta, Canada between 2008 and 2019. An individual’s residence (rural/urban/metropolitan) was defined from postal codes using 4 different methods: residence defined at 1-year before first metformin (this served as the reference model), comparison 1- stable residence for 3 years before first metformin, comparison 2– residence as time-varying (during the outcome observation window), and comparison 3 - nested case control (residence closest to the index date after identifying cases and controls). Multivariable Cox proportional hazard and logistic regression models were constructed to examine the association between residence definitions and all-cause mortality. Results We identified 157,146 new metformin users (mean age of 55 years and 57% male) and 8,444 (5%) deaths occurred during the mean follow up of 4.7 (SD 2.3) years. There were few instances of moving after first metformin; 2.6% of individuals moved to a smaller centre (metropolitan to urban or rural, or urban to rural) and 3.1% moved to a larger centre (rural to urban or metropolitan, or urban to metropolitan). The association between rural residence and all-cause mortality was consistent (aHR:1.18; 95%CI:1.12–1.24), regardless of the method used to define residence. Conclusions The method used to define residence in a population of adults newly treated with metformin for type 2 diabetes has minimal impact on measures of all-cause mortality, possibly due to infrequent migration. The observed association between residence and mortality is compelling but requires further investigation and more robust analysis.